Association between serum uric acid levels and peripheral artery disease in Chinese adults with hypertension - Han, Fengyu; Yu, Chao; Hu, Feng; Zhou, Wei; Wang, Tao; Zhu, Linjuan; Huang, Xiao; Bao, Huihui; Cheng, Xiaoshu (Frontiers in Endocrinology, 2023)
Background: Higher serum uric acid (SUA) was possible to further cause gout, which is principally characterized by arthritis due to monosodium urate crystal deposition in the lower extremities. And high levels of SUA have been linked to endothelial dysfunction, oxidative stress, and inflammation, all of which are involved in the pathogenesis of peripheral artery disease(PAD). To date, the relationship between SUA levels and PAD is still poorly understood.Method: An analysis of 9,839 Chinese adults with essential hypertension from the ongoing China H-type Hypertension Registry Study was conducted in this crosssectional study. Patients with an ABI ≤0.9 was diagnosed as PAD. Hyperuricemia was defined as SUA levels >420 mol/L in men and >360 mol/L in women. The association between SUA levels and PAD was evaluated using multivariable logistic regression models based on odds ratios (ORs) and their 95% confidence intervals (CIs).The enrolled subjects ranged in age from 27 to 93 years, with a mean age of 63.14 ± 8.99 years. The proportion of male patients was 46.22%, and the prevalence of hyperuricemia was 50.72%. In males, hyperuricemia was positively associated with the risk of PAD (adjusted OR per SD increase: 1.72, 95% CI 1.17 to 2.53, P =0.006). Males in the highest SUA tertile were significantly more likely to have PAD (adjusted OR: 2.63, 95% CI 1.42 to 4.86, P = 0.002; P for trend = 0.001). However, this positive relationship was not observed in females (adjusted OR: 1.29, 95% CI 0.77 to 2.17, P = 0.327; P for trend = 0.347).According to this cross-sectional study, higher SUA levels were positively associated with PAD in male hypertensive patients, while this positive relationship disppeared in female participants.